Analysis of Postmortem Examination in Exhumed Cases Done in and Around Bangalore, India for 10 Years: A Retrospective Study - V, Suresh; S, Jyothi; Cyriac, Agnes J (International Journal of Medical Toxicology and Forensic Medicine, 2022)
Background: Exhumation is the process of removing the dead body from the grave. The reasons and time limit for exhumation may vary from country to country. After receiving a request from the Magistrate, exhumation followed by postmortem is done to gain essential evidence. To comprehensively analyze the exhumation cases done in Victoria Hospital, Bangalore, and how exhumation followed by postmortem examination aids in finding the cause of death. Methods: All cases of exhumations performed for 10 years (from January 1, 2012, to December 31, 2021) in the Department of Forensic Medicine and Toxicology, Victoria Hospital, Bangalore, were studied retrospectively. The essential data were collected from requisition forms, exhumation, and postmortem reports. The results were obtained after tabulating, and data were analyzed with an observational method. Results: A total of 37 exhumation cases were done during the study period. Young males in the age group of 21 to 30 years were the major population. Out of 37 cases, the cause of death was established in 25 cases (68%). Conclusion: Analysis of postmortem examination in exhumed cases gives much information from a medicolegal point of view to determine the cause and reveal the mysteries behind the manner of death. Hence it is not a vain procedure.